1983
DOI: 10.1002/chin.198305238
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: β‐CARBOLINES: SYNTHESIS AND NEUROCHEMICAL AND PHARMACOLOGICAL ACTIONS ON BRAIN BENZODIAZEPINE RECEPTORS

Abstract: Die Aminocarbonsäuren (I) werden zu den Tetrahydro‐β‐carbolinen (II) cyclisiert, deren Dehydrierung die β‐Carboline (III) ergibt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…29 In Vivo Studies: Proconvulsant, Anticonvulsant, and Diazepam Antagonism Action. Groups of 10 mice were injected intraperitoneally (0.1 mL) with graded doses of the compounds (up to the highest dose of 250 mg/kg), suspended in 20% dilute Emulphor-80% saline solution (vehicle) (dilute Emulphor is Emulphor diluted 1:1, w/w, with ethanol), or an equal volume of the vehicle, followed 30 min later by PTZ at 40 or 80 mg/kg to assess the proconvulsant and anticonvulsant actions, respectively, as described by Trudell et al 52 Antagonism of the anticonvulsant effects of diazepam was carried out as described by Cain et al 53 Groups of 10 mice were injected with diazepam (2.5 mg/kg ip) followed 10 min later by administration of graded doses of the test compound or vehicle. Fifteen minutes after injection of the compound, animals were injected with PTZ (80 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…29 In Vivo Studies: Proconvulsant, Anticonvulsant, and Diazepam Antagonism Action. Groups of 10 mice were injected intraperitoneally (0.1 mL) with graded doses of the compounds (up to the highest dose of 250 mg/kg), suspended in 20% dilute Emulphor-80% saline solution (vehicle) (dilute Emulphor is Emulphor diluted 1:1, w/w, with ethanol), or an equal volume of the vehicle, followed 30 min later by PTZ at 40 or 80 mg/kg to assess the proconvulsant and anticonvulsant actions, respectively, as described by Trudell et al 52 Antagonism of the anticonvulsant effects of diazepam was carried out as described by Cain et al 53 Groups of 10 mice were injected with diazepam (2.5 mg/kg ip) followed 10 min later by administration of graded doses of the test compound or vehicle. Fifteen minutes after injection of the compound, animals were injected with PTZ (80 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…33 In Vivo Studies: Procovulsant, Anticonvulsant, and Diazepam Antagonism Action. Groups of 10 mice were injected intraperitoneally (0.1 mL) with graded doses of the compounds (up to the highest dose of 250 mg/kg), suspended in 20% dilute Emulphor-80% saline solution (vehicle) (dilute Emulphor is Emulphor diluted 1:1, w/w, with ethanol), or an equal volume of the vehicle followed 30 min later by PTZ at 40 or 80 mg/kg to assess the proconvulsant and anticonvulsant actions, respectively, as described by Trudell et al 58 Antagonism of the anticonvulsant effects of diazepam was carried out as described by Cain et al 59 Groups of 10 mice were injected with diazepam (2.5 mg/kg ip) followed 10 min later by administration of graded doses of test compound or vehicle. Fifteen minutes after injection of the compound, animals were injected with PTZ (80 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…The isodensity version of Polarized Continuum Model (PCM) [22,23] have been used to get the thermochemical parameters such as Solvation Free Energy and the quantum chemical parameters such as Energy Gap, electronic chemical potential (µ), global hardness (η), electrophilicity (ω) and the maximum charge transfer index (ΔNmax) to evaluate the effect on the chemical reactivity behavior of selected βC and their 1-substituted derivatives. Geometry optimizations and frequency calculations have been carried out with three basis set just as 6…”
Section: Methodsmentioning
confidence: 99%
“…Initially, βC-3carboxylates have been studied because of their antagonist characteristics on BzR (benzodiazepine receptors) [3], after that, it is realized that these compounds have also acted as BzR inverse agonist [4], also it is to be reminded the inverse agonists such as βCCM and βCCE don't act on identical receptor sites [5]. Cain, M., and co-workers, with their study on βC acting on brain BzR have been proved that the full aromatic βC's have been more potent than their corresponding THβC's, also have been shown that this group compounds ability to bind Benzodiazepine receptor has increased with the substitution at the C-3 position [6]. In another work focused on BzR, it has been shown that the affinity is augmented with the ester formation at the substituent group at C-3 position of the interested compound, but this strongly depends on molecular size, hydrophobic and electronic properties of the ester type [7].…”
Section: Introductionmentioning
confidence: 99%